Effects of various surface treatments on the biaxial flexural properties of yttria-stabilized zirconia ceramics - Teerthesh Jain; Amit Porwal; Bhushan R Bangar; Soniya Niras Patil; Elanangai E; Ranu Bhandari; Abhishek Singh Nayyar (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of the present study was to evaluate and compare the influence of different surface treatments and their cumulative effects on the biaxial flexural properties and phase transformation of yttria-stabilized zirconia ceramics. Materials and Methods: A total of fifty specimens were fabricated by computer-aided design/computer-aided manufacturing machining from Cercon®. The samples were divided into five groups following different surface treatments as control (C), air particle abrasion (Si), mechanical loading (ML), low-temperature degradation (LTD), and cumulative treatment (CT) groups. Statistical Analysis Used: The results were analyzed by two-way ANOVA and Tukey's honestly significant difference (HSD) test. Two-way ANOVA was used to find significance between the test and the control groups. Tukey's HSD test was carried out to determine any significant difference among the groups. Results: The highest biaxial flexural strength was observed in the Si group (950.2 ± 126.7 MPa) followed by the LTD group (861.3 ± 166.8 MPa), CT group (851.2 ± 126.5 MPa), and the least with the ML group (820 ± 110 MPa). Significant difference was observed in two-way ANOVA test. Tukey's HSD test showed that there was a significant difference (P ≤ 0.05) between the C and Si groups and C and LTD groups; however, no significant difference was observed (P ≥ 0.05) between the C and ML groups and C and CT groups. X-ray diffraction analysis showed that the control group consisted of 100% tetragonal zirconia while the maximum amount of monoclinic phase was obtained after the LTD treatment. Conclusions: Air particle abrasion with CoJet Sand, LTD, and CTs had no negative impact on biaxial flexural strength indeed it increased the biaxial flexural strength. Hence, these surface treatments can be done in routine clinical practice to improve the performance of ceramic restorations.